Win at all costs : inside Nike running and its culture of deception - Hart, Matt (Dey St., an imprint of William Morrow, 2020)
"Game of Shadows meets Shoe Dog in this explosive behind-the-scenes look that reveals for the first time the unsettling details of Nike's secret running program-the Nike Oregon Project. In May 2017, journalist Matt Hart received a USB drive containing a single file-a 4.7-megabyte PDF named "Tic Toc, Tic Toc. . . ." He quickly realized he was in possession of a stolen report prepared a year earlier by the United States Anti-Doping Agency (USADA) for the Texas Medical Board, part of an investigation into legendary running coach Alberto Salazar, a Houston-based endocrinologist named Dr. Jeffrey Brown, and cheating by Nike-sponsored runners, including some of the world's best athletes. The information Hart received was part of an unfolding story of deception which began when Steve Magness, an assistant to Salazar, broke the omertà-the Mafia-like code of silence about performance-enhancing drugs among those involved-and alerted the USADA. He was soon followed by Olympians Adam and Kara Goucher who risked their careers to become whistleblowers on their former Nike running family in Beaverton, Oregon. Combining sports drama and business exposé, Win at All Costs tells the full story of Nike's running program, uncovering a corporate win-at-all-costs culture"--